Time-dependent global attractors for the strongly damped wave equations with lower regular forcing term - Mei, Xinyu; Sun, Tao; Xie, Yongqin; Zhu, Kaixuan (Topological Methods in Nonlinear Analysis, 2022)
In this paper, based on a new theoretical framework of time-dependent global attractors (Conti, Pata and Temam CPT13), we consider the strongly damped wave equations ε(t)u_tt-Δ u_t-Δ u+f(u)=g(x) and establish the existence of attractors in H_t=H_0^1(Ω)× L^2(Ω) and V_t=H_0^1(Ω)× H_0^1(Ω), respectively.